FUNCTIONAL AND PRAGMATIC APPROACHES IN ACADEMIC DISCOURSE: THEORETICAL-METHODOLOGICAL FOUNDATIONS (Scientific journal of the Fergana State University, 2026)
The article analyzes theoretical-methodological foundations of studying functional and pragmatic nature of academic discourse. Integrative model of systemic-functional grammar and speech acts theory is created.